Uzbekistan Universal School Is Based On The Training Of Specialist Personnel For Physical Education Education And Culture (Eurasian Journal of Learning and Academic Teaching, 2022)
The article provides a description of the methodology for the study and organization of work experience in the preparation of owners of physical culture from physical education in secondary schools of Uzbekistan on a competent basis. Also, the school is given a classification of mass physical culture and sports activities, which students with great enthusiasm perform on a public basis.